A peculiar mixture: German-language cultures and identities in eighteenth-century North America - Stievermann, Jan; Scheiding, Oliver (The Max Kade Research Institute series: Germans beyond Europe, 2013)
"A collection of essays that explore the transatlantic German cultures and identities of the colonial period"--Provided by publisher